FAKTOR PENENTU PEMILIHAN VARIAN BAHASA OLEH MULTIBAHASAWAN ETNIS MADURA DI JEMBER DALAM OBROLAN - Bambang Wibisono (Humaniora, 2007)
This article explores the choice of linguistic repertoire in conversation by the multilingual Maduranese ethnic community of Jember. This study which is done by using sociopragmatic approach shows that the use of language variations is determined by social, psychological, cultural, and educational factors each of which can further be analysed into several subfactors.